Sound Design in Popular Music: Gen Z Perspective and Perception - Ferdian, Robby; Hidayat, Hengki Armez; Sari, Ayuthia Mayang; Putra, Irdhan Epria Darma; Fitria, Ressy; Fauzi, Fakhri; Lailiyah, Malikhatul (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
This study explores Generation Z's understanding and perception of sound design in popular music, focusing on how this concept influences their music-listening experiences and emotional responses. Sound design, encompassing audio production quality, sound effects, and waveform processing, is critical in shaping diverse auditory experiences. However, the depth of understanding of sound design among Generation Z varies widely, presenting an opportunity to bridge knowledge gaps in music education. Using a quantitative descriptive approach, a survey was conducted among students with music education backgrounds to assess their familiarity with sound design concepts. The findings reveal diverse levels of comprehension, with some respondents recognizing the term "sound design" but lacking a clear understanding, while others demonstrated a deeper knowledge of its components and significance. Participants identified key elements of sound design, such as the importance of production quality, creative use of sound effects, and manipulating audio waveforms, as pivotal in enhancing the listening experience. A novel aspect of this study is examining how sound design impacts emotional engagement with music. Most respondents reported that sound design enhances the emotional depth of songs and makes the music more immersive and enjoyable. Interestingly, while many felt that sound design influenced their music preferences, a subset of respondents remained unaffected. This research highlights a strong interest among Generation Z in learning more about sound design, suggesting the need for educational initiatives that integrate sound design into music curricula.